Rapid, Direct Tissue Culture Test for Toxigenicity of Corynebacterium Diphtheriae - Laird, Walter (1973)
A method for testing toxigenicity of Corynebacterium diphtheriae in tissue culture is described. The technique, called the colony overlay test (COT), involves inoculating material from an isolated colony of C. diphtheriae to a small area on the surface of an agar medium which overlays a monolayer of toxin-susceptible HeLa cells. If toxin is produced during incubation at 37 C, it diffuses to the tissue monolayer and destroys the cells below the inoculation site. Twenty-four hours after inoculation, organisms are killed and tissue cells are fixed with formaldehyde. The agar overlay is then removed, and the monolayer is stained with crystal violet. Toxin-affected areas fail to stain or stain poorly. A second plate with antitoxin incorporated in the overlay serves as a control for specificity. Forty-eight strains of C. diphtheriae were tested by the COT, guinea pig, and in vitro, gel diffusion tests. The COT is as specific as the other two tests, is easy to read, and can be used to test large numbers of isolates for toxin action more conveniently than by animal inoculation.